Tổng hợp và thử hoạt tính gây độc tế bào ung thư của một số dẫn chất Isatin mang khung 2-(3-Oxo-2,3-Dihydro-4H-benzo[b][1,4]oxazin-4-yl)Acetohydrazid mới / Trần Phương Thảo, Cao Việt Phương - Trần, Phương Thảo
A new isatine series of 2-(3-oxo-2,3-dihydro-4H-benzo[b][1,4]oxazin-4-yl)acetohydrazides were designed, synthesized and evaluated cytotoxicity. The compounds were obtained by a 4 steps synthesis with well-known reactions. Of the seven synthesized compounds, two (5a, 5b) exhibited significant inhibitivity on cancer cell growth and moderate cytotoxicity against three human cancer cell lines (SW620, colon cancer; PC-3, prostate cancer; NCI-H23, lung cancer), with IC50 values ranging from 14.84 to 31.92 µM.